Andro-gynecology and psychosomatic medicine. Aspects of gynecological - Guerrero, Carlos (2015)
It is well know that sexual alterations produce profound psychic changes which in turn can give origen to organic modífications. There are into relationship among the organic, functional and animic levels of the individual changes, in the sexual or non sexual spheres can influence those aspects of the subject or viceversa. Gynecological and andrological changes as a cause of psychosomatic alterations are discussed. The following types of processes are commented: 1° Gynecological disease produced extra-gynecological manifestations. Many of these patients remain unknown having gynecological maladies. 2° Patients with no gynecological disease and gynecological symptoms. Pseudo-gynecological patients. 3° Patients with gynecological disease and gynecological symptoms.